A simple method to freely adjust the crystalline phase and micro-morphology of NixPy compounds. (20th July 2017) - Lu, Shaoxiang; Xu, Hanghui; Gao, Bingying; Ren, Lili
Abstract : Different crystalline phase of Ni x P y compounds with different morphology were successfully fabricated via a hydrothermal method assisted by urea. Abstract : Different crystalline phase and micro-morphology Ni x P y compounds have been successfully synthesized via a hydrothermal reaction assisted by urea. The phase transition and morphology change of Ni x P y compounds were investigated via X-ray diffraction (XRD), inductively coupled plasma atomic emission spectrometry (ICP), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results showed that two different crystalline phases of Ni x P y compound could be obtained only by adjusting the amount of addition of urea. Moreover, the micro-morphology varied from irregular bulks to fold, beehive-like shape and then to particle-aggregated and finally to a 3D-network with an increase in the amount of urea, which exhibited much higher hydrodechlorination (HDC) activity on trichloroethylene (TCE) than Ni2 P without addition of urea. In a word, adding urea is a facile way to prepare Ni x P y compounds with a controllable crystalline phase and micro-morphology.